Large-Area Uniform 1-nm-Level Amorphous Carbon Layers from 3D Conformal Polymer Brushes. A "Next-Generation" Cu Diffusion Barrier? - Kang, Yun-Ho (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.